(untitled) (Research, Society and Development, 2022)
The lack of energy in rural properties, in many cases, it causes the loss of agricultural products dependent on electrification. The aim of this study as minimize losses arising from poor electricity supply for small and medium-sized producers, through the economic feasibility analysis of the implementation of an energy backup system for the milk production process in the central-eastern of São Paulo - Brazil. The backup equipments proposed in the present work has different operating principles, since the batteries are charged and store charges from the solar production, and the motor generator converts the chemical energy of the fuel into electrical energy, and together, both will provide the electricity needed to maintain dairy production activities on the farm analyzed. From the proposed project, the economic analysis was performed for the implementation estimated in two scenarios of the systems. The financial projection considered the minimum attractiveness rate (TMA) equal to the Selic rate of 6.24%. Under such conditions the best return on invested capital was obtained for the solar system and batteries, with return in 7 years and 1 month in payback discounted in the pessimistic scenario and 8 years and 4 months in payback discounted in the reference scenario. The return on capital obtained within the lifetime of the equipment prove the viable and profitable of the installation of energy backup systems to small rural producers.